A Krukenberg Tumor from an Occult Intramucosal Gastric Carcinoma Identified during an Autopsy - Yoshiaki Nakamura; Ayako Hiramatsu; Takafumi Koyama; Yu Oyama; Ayuko Tanaka; Koichi Honma (Case Reports in Oncological Medicine)
A healthy 45-year-old Japanese female developed right pleural effusion, ascites, and a pelvic mass. Bilateral salpingo-oophorectomy resolved the pleural effusion and ascites. Histopathological examination of the ovaries showed bilateral Krukenberg tumors with signet-ring cell carcinoma (SRCC). Extensive testing including upper and lower gastrointestinal endoscopy and whole-body imaging did not detect the primary lesion. Six months after bilateral salpingo-oophorectomy, the patient developed multiple osteoblastic bone lesions in the spine, pelvis, and femurs. A biopsy of the bone marrow showed SRCC. We administered four cycles of S-1 and cisplatin, resulting in the shrinkage of osteoblastic lesions; she remained stable for a year. Then, she developed disseminated intravascular coagulation with disease progression in the bones. Although she was treated with paclitaxel, the disseminated intravascular coagulation progressed, and she died in a month. During the autopsy, microscopic examination revealed four foci of intramucosal gastric SRCC and healthy macroscopic gastric mucosa.